Injury mechanism classification in soccer videos - Ramana Murthy, O. V.; Goecke, R. (IEEE/CVF International Conference on Computer Vision, 2015)
Soccer is a very popular sport but also has a high rate of injuries. In this paper, player falling events in Soccer videos are classified into five major categories. These categories have been identified by Soccer coaches as the major mechanisms behind injuries of the players. Automatic detection of these events will be useful to the coaches to impart individual training to the players that will enhance their physical strength and also the playing style. A Bag-of-Words framework is used and a baseline classification accuracy is established.